Relationship between Customers' Loyalty and Income: Preliminary Research - Igor Klopotan; Kristina Vrhovec-Žohar; Edita Mahič (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
Customer relationship management has a great role in customers' loyalty and satisfaction. However, it is questionable if companies are facing their customers with adequate care. Research that analyzes income and its impact to customers' loyalty, especially in post-transition countries is scare. This paper investigates customers' attitudes towards selected loyalty determinants. In order to achieve the goal, empirical research on the sample of Croatian customers has been conducted. The respondents were classified into three groups regarding income level and then compared using Kruskall-Wallis test.
Keywords: C1; D3; M00; 330; customer relationship management; economics; customer loyalty management